Analisis Perilaku Bullying dalam Perspektif Sila Kedua Pancasila: An Analysis of Bullying Behavior from the Perspective of the Second Precept of Pancasila - Leonard Brahmandika (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2026)
The incidence of bullying has risen annually, driven by factors like family, peers, social environments, and media. Public outrage has intensified as even deceased victims face bullying, prompting calls for strict punishment due to the perpetrators' inhumane behavior. This qualitative literature review aims to analyze how bullying contradicts the second principle of Pancasila, Just and Civilized Humanity. The findings indicate that bullying violates this principle because it demonstrates a severe lack of empathy, reflecting a poor understanding of how to treat others with basic human dignity.